(untitled) (Journal of the College of Basic Education, 2025)
Objective: This study aims to identify the role of kindergartens in developing communication skills in children with language learning difficulties. Methodology: A qualitative approach is used. To achieve the study’s objectives, interviews are conducted to gather information. The study sample consists of (10) kindergarten teachers, selected through a convenience sampling method. Results: The study results show the significant role of kindergartens in developing communication skills in children with language learning difficulties. The results also indicate that teaching quality, providing a stimulating classroom environment, and parental cooperation play a crucial role in improving communication skills. Conclusion: The study recommends developing specialized training programs for teachers to equip them with the necessary skills and tools to deal with this category of children, ensuring they receive the best educational care.